2019
DOI: 10.1002/cssc.201802130
|View full text |Cite
|
Sign up to set email alerts
|

Task‐Specific Catalyst Development for Lignin‐First Biorefinery toward Hemicellulose Retention or Feedstock Extension

Abstract: A catalytic reductive fractionation method for lignocellulosic biomass, termed lignin‐first biorefinery, has emerged, which emphasises preferential depolymerization of the protolignin. However, in most studies, the lignin‐first biorefinery is only effective for hardwood that has a high syringyl/guaiacol (S/G) ratio of lignin building blocks, and the degradation of hemicellulose also takes place simultaneously to a certain degree. In this study, two task‐specific catalysts were developed to realize hemicellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Although depolymerization of these technical lignins is possible, it typically requires harsh conditions that result in a complex mixture of products. This limitation is the result of the severe processing conditions applied during fractionation, which leads to a lignin with a complex, condensed C–C bonded chemical structure, thus hindering selective depolymerization into selected aromatic monomers. The second approach is to avoid condensation reactions and address lignin depolymerization at an early stage of the lignocellulose conversion process, often termed lignin-first or early-stage lignin biorefining. This can be achieved by either performing the fractionation under mild conditions to obtain lignins with a more native-like C–O bonded structure by preserving the β-aryl ether units or by integrating the depolymerization into the fractionation process. An example of the latter is the application of reductive fractionation to extract and depolymerize lignin into specific alkyl-phenolics in high yield. Reductive depolymerization is only one of many selective lignin depolymerization methods and yields a specific selection of phenolic products. , For the implementation of higher value lignin products in a biorefinery scheme, a more diverse chemical platform is desired . There are many other elegant depolymerization methods that cannot be implemented during fractionation, but rather require isolated lignins .…”
Section: Introductionmentioning
confidence: 99%
“…Although depolymerization of these technical lignins is possible, it typically requires harsh conditions that result in a complex mixture of products. This limitation is the result of the severe processing conditions applied during fractionation, which leads to a lignin with a complex, condensed C–C bonded chemical structure, thus hindering selective depolymerization into selected aromatic monomers. The second approach is to avoid condensation reactions and address lignin depolymerization at an early stage of the lignocellulose conversion process, often termed lignin-first or early-stage lignin biorefining. This can be achieved by either performing the fractionation under mild conditions to obtain lignins with a more native-like C–O bonded structure by preserving the β-aryl ether units or by integrating the depolymerization into the fractionation process. An example of the latter is the application of reductive fractionation to extract and depolymerize lignin into specific alkyl-phenolics in high yield. Reductive depolymerization is only one of many selective lignin depolymerization methods and yields a specific selection of phenolic products. , For the implementation of higher value lignin products in a biorefinery scheme, a more diverse chemical platform is desired . There are many other elegant depolymerization methods that cannot be implemented during fractionation, but rather require isolated lignins .…”
Section: Introductionmentioning
confidence: 99%
“…Liquid alkylcyclohexanes, arenes, polyols, and furfural derivatives were produced [70,71]. The latest novel results were carried out using new catalysts [80,87,88] and by developing task-specific catalysts for hardwood and softwood [86], chemodivergent hydrogenolysis (for propyl-or propanol-methoxyphenol production) [87], membrane filtration [83], and applying new solvents/stabilization agent (dimethyl carbonate) [92]. The first integrated techno-economic assessment of a biorefinery process revealed that using only waste wood as feedstock can make the investment profitable [101].…”
Section: Discussionmentioning
confidence: 99%
“…Two task-specific catalysts were developed for RCF: Mo x C/CNT for hardwood, and Ru/CMK-3 for softwood and grass. Using Mo x C/CNT for apple wood led to a carbohydrate (both cellulose and hemicellulose) retention degree in solid product close to theoretical maximum and a delignification degree as high as 98.1% with 42% lignin monomers yield (entry 67 in Table 1 ) [ 86 ].…”
Section: Chronological Overviewmentioning
confidence: 99%
“…Although previous studies have demonstrated that RCF could be an effective technique for the production of high-yield LDPMs and high holocellulose retention, the RCF process still presents challenges that should be carefully addressed. First, as summarized in Table S1, most of the previous studies used highly loaded precious metal-supported catalysts (e.g., 5 wt % Ru/C, 5 wt % Ru/SiC, 5 wt % Ru/CMK-3, 2 wt % Ru/α-HfP, 5 wt % Pd/C, , 5 wt % Zn/Pd/C, , 1 wt % Pt/γ-Al 2 O 3 , and 5 wt % Pt/C). The extreme scarcity and high cost of noble metals (e.g., Pt, 50.86 USD/g; Pd, 31.99 USD/g; and Ru, 9.27 USD/g) could be major drawbacks that prevent the practical-scale production of biofuel, and thus, it would be desirable to develop highly efficient and inexpensive non-noble metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme scarcity and high cost of noble metals (e.g., Pt, 50.86 USD/g; Pd, 31.99 USD/g; and Ru, 9.27 USD/g) could be major drawbacks that prevent the practical-scale production of biofuel, and thus, it would be desirable to develop highly efficient and inexpensive non-noble metal-based catalysts. To avoid the use of precious noble metals, some non-noble metal-based catalysts, such as Ni-based (e.g., 5–15 wt % Ni/C, ,, Raney Ni, ,,, 21 wt % Ni/Al 2 O 3 , 14 wt % Ni@ZIF-8, and 33.6 wt % Ni@Al 2 O 3 /AC), Co-based (e.g., Co-phen/C), and Mo-based (e.g., 10 wt % Mo x C/CNT, MoS 2 , and 5.7 wt % MoO x /SBA-15) catalysts have been proposed for the RCF of woods. However, the LDPM yields obtained over non-noble metal-based catalysts (10–45 C %, Table S1) were lower than those achieved over precious noble metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%